Treatment Adherence Among Patients Undergoing Hemodialysis of Selected Hospitals of Rupandehi - Shrestha, Pragya; Shrestha, Neelam; Rana, Ikshaya (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION Chronic kidney disease (CKD) is a major public health problem in Nepal. Adherence is the crucial factor in determining the morbidity and mortality of hemodialysis patients. MATERIAL AND METHODS A cross-sectional study was conducted to find out the hemodialysis adherence among 125 hemodialysis patients of Universal College of Medical Sciences-Teaching Hospital and Crimson Hospital, Rupandehi. The data was collected by enumerative sampling using semi-structured interview schedule. The duration of the study was from June 16, 2019 to August 2, 2019. The data was analyzed by using descriptive and inferential statistics with SPSS software version 16.0. RESULTS The study revealed 56.8% were adherent to haemodialysis in general. Likewise 62.7%, 77.1%, 74.6% and 48.3% were adherent to haemodialysis schedule, diet restriction, fluid restriction and medication respectively. There was statistically significant association between level of adherence to haemodialysis and education level (p=0.020), adequacy of family monthly income for haemodialysis (p=0.007), presence of care taker to haemodialysis centre (p=0.057) and haemodialysis hours in a session (p=0.002). CONCLUSION It is concluded that the haemodialysis adherence among patients is good in general but poor adherence to medicine. The adherence is influenced by education, family monthly income, presence of care taker and haemodialysis hours in a session. Hence it emphasizes on need for educating patients to enhance adherence to haemodialysis.